THE NUCLEAR AND MAGNETIC STRUCTURE OF "WHITE RUST"-FE(OH0.86D0.14)2 - Parise J.B.; Marshall W.G.; Smith R.I.; Luiz H.D.; Möller H. (My University, 2000)
The structure of Fe(OH0.86,OD0.14)2 was refined by applying the Rietveld technique to neutronpowder diffraction data collected at 300, 150, and 10 K. The nuclear structure, of the CdI2 type (P3–m1) and isostructural with Mg, Ca, Mn, Ni, and β-Co(OH)2, is maintained over the range of tem-peratures studied. At 10 K, the magnetic structure is ordered antiferromagnetically, with the magneticmoments aligned in the basal plane. The refined Fe2+ magnetic moment magnitude is 3.50(4) μB.This magnetic structure (space group P2c1–) is unique amongst those encountered in the transitionmetal dihydroxides, for which the moment is either directed along the c axis [β-Co(OH)2 and Ni(OH)2],or at least has a considerable component along this direction [Mn(OH)2]. The dependence of thestrength of potential hydrogen bonds with temperature is discussed.